The impacts of university management on academic work: Reform experiences in Austria and Germany - Barbara Kehm; Ute Lanzendorf (Management Revue, 2007)
This contribution analyses the impacts of managerial governance on academic work, and more especially on research, comparing German and Austrian universities. First, recent reforms of university governance in the two countries are summarized. Second, the degree of implementation of managerial governance at universities is analysed as well as its effects on decision-making and on the organisation of research by individual academics, drawing on 39 interviews conducted in the 2 countries. Empirical evidence suggests that (a) managerial decision-making structures have been implemented at the central level; (b) deans basically see their role as protecting academics from pressures emanating from managerial interventions of university leadership; and (c) restrictions experienced by individual academics with respect to their personal research agendas are due to shortages of resources rather than to the newlyintroduced mechanisms of external guidance or competitive pressure. As a conclusion, the growing importance of non-academically defined criteria for research performance is highlighted as a major consequence of the introduction of university management which could, in future, make traditional academic quality standards less relevant.
Keywords: 650; new public management; university management; university research; international comparison; empirical research; Europe